Online Attraction: Investigating Digital Marketing’s Impact on Shopping Behavior in Shopee - Lim, Zi Kian; Sim, Choon Ling; Lok, Yee Huei; Ling, Hee Yang; Lim, Xian Bei; Lim, Yee Teng; Lin, Yi Tong; Ali, Anees Jane; Mui Hung Kee, Daisy (Advances in Global Economics and Business Journal, 2025)
This study investigates the impact of digital marketing on consumer shopping behavior on Shopee. Shopee is one of the famous e-commerce platform in Southeast Asia and Taiwan, based on downloads, monthly active users, and total time spent on the app for Android users. In this study, we examine mobile marketing, content marketing, social media marketing, and email marketing as our independent variables. We analyze the relationship between these four variables and consumer shopping behavior on Shopee. We collect the data by distributing a questionnaire to 150 Shopee users. Our findings show that digital marketing influence consumer shopping behavior significantly except for email marketing. We found that digital marketing will attract the consumer to visit Shopee. This enhances consumer trust and purchase intention, particularly among younger consumers, leading to greater engagement and improved sales performance on Shopee.